PEMBERDAYAAN EKONOMI RAKYAT MELALUI PENGUATAN MANAJEMEN ORGANISASI DI INDONESIA - Sofyan Hadi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
Many Non-Governmental Organization (NGO) or NGO implementing the program in rural and urban environments. Their activities are characterized by uplift and empower the poorest people, to encourage wider participation, not bureaucratic and in need of a low cost, and many do experiment in community. The issue is how Non Governmental Organization (NGO) perform its activities and how the government response to the role of social transformation. To address this problem, theoretically use interactive theory, integrative of Gramcian and Community Development of Jim Ife and Susan Kenny. Discussion focused on the responses of government, as is often the activity of NGOs opposed to government policy.